TEZАURUSLАR VА ULАRNI TАHLIL QILISH TАMОYILLАRI («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
This article discusses thesauruses, their importance in creating dictionaries, and principles of classification. The advantages of thesaurus dictionaries are explained with the help of examples.
Keywords: thesaurus, dictionary, semantic connection, WordNet.